2021
DOI: 10.1177/08912432211001287
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and The Gender Gap in Employment Among Parents of Young Children in Canada

Abstract: Economic and social disruptions of the COVID-19 pandemic have important implications for gender and class inequality. Drawing on Statistics Canada’s monthly Labour Force Survey, we document trends in gender gaps in employment and work hours over the pandemic (February–October 2020). Our findings highlight the importance of care provisions for gender equity, with gaps larger among parents than people without children, and most pronounced when care and employment were more difficult to reconcile. When employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 17 publications
4
55
0
2
Order By: Relevance
“…results have been reported for the United Kingdom (Andrew et al 2020) and Canada (Fuller & Qian 2021). Against the backdrop of a conservative gender regime and the predominant role of mothers as secondary earners (Riederer & Berghammer 2020)combined with a sudden increase in family-based care work during the pandemic (Berghammer 2021 in this Special Issue) -we may expect to see a similar pattern in Austria.…”
Section: Parental Employmentsupporting
confidence: 69%
“…results have been reported for the United Kingdom (Andrew et al 2020) and Canada (Fuller & Qian 2021). Against the backdrop of a conservative gender regime and the predominant role of mothers as secondary earners (Riederer & Berghammer 2020)combined with a sudden increase in family-based care work during the pandemic (Berghammer 2021 in this Special Issue) -we may expect to see a similar pattern in Austria.…”
Section: Parental Employmentsupporting
confidence: 69%
“…Evidence from the United States (Lofton et al, 2021;Landivar et al, 2020) shows that at the start of the pandemic fathers saw their employment fall less than women and childless men and the recovery of jobs has been more pronounced for men and childless women than for mothers. Similar results have been reported for the UK (Andrew et al, 2020) and Canada (Fuller & Qian, 2021). We will test if mothers were more likely to lose their jobs or to register for short-time work (thus to record income losses) than women as part of childless couples or men also in Austria.…”
Section: Gender Perspectivesupporting
confidence: 62%
“…In the UK, during the first lockdown period from April to May 2020, among parents with children aged between 4 and 15, mothers were found to be more likely to be laid off, furloughed, or quit their jobs [ 21 ]. Similarly, in Australia [ 6 ], Canada [ 22 ], and the US [ 23 ], mothers with young children experienced a larger change in their paid work time or were more likely to leave their jobs. On the other hand, several studies have reported improvements in the domestic division of labor: the increase in domestic work was larger for men than for women during the lockdown period in Australia [ 6 ], Canada [ 24 ], France [ 25 ], and the US [ 26 ].…”
Section: The Impacts Of Covid-19 and Its Related Measuresmentioning
confidence: 99%